Mesopredator Management: Effects of Red Fox Control on the Abundance, Diet and Use of Space by Feral Cats - Molsher, Robyn; Newsome, Alan E.; Newsome, Thomas M.; Dickman, Christopher R. (PloS one, 2017)
Apex predators are subject to lethal control in many parts of the world to minimize their impacts on human industries and livelihoods. Diverse communities of smaller predators-mesopredators-often remain after apex predator removal. Despite concern that these mesopredators may be 'released' in the absence of the apex predator and exert negative effects on each other and on co-occurring prey, these interactions have been little studied. Here, we investigate the potential effects of competition and intraguild predation between red foxes (Vulpes vulpes) and feral cats (Felis catus) in south-eastern Australia where the apex predator, the dingo (Canis dingo), has been extirpated by humans. We predicted that the larger fox would dominate the cat in encounters, and used a fox-removal experiment to assess whether foxes affect cat abundance, diet, home-range and habitat use. Our results provide little indication that intraguild predation occurred or that cats responded numerically to the fox removal, but suggest that the fox affects some aspects of cat resource use. In particular, where foxes were removed cats increased their consumption of invertebrates and carrion, decreased their home range size and foraged more in open habitats. Fox control takes place over large areas of Australia to protect threatened native species and agricultural interests. Our results suggest that fox control programmes could lead to changes in the way that cats interact with co-occurring prey, and that some prey may become more vulnerable to cat predation in open habitats after foxes have been removed. Moreover, with intensive and more sustained fox control it is possible that cats could respond numerically and alter their behaviour in different ways to those documented herein. Such outcomes need to be considered when estimating the indirect impacts of fox control. We conclude that novel approaches are urgently required to control invasive mesopredators at the same time, especially in areas where apex predators are absent.